2013
DOI: 10.1021/la400801s
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Frost Formation on Lubricant-Impregnated Surfaces

Abstract: Frost formation is a major problem affecting a variety of industries including transportation, power generation, construction, and agriculture. Currently used active chemical, thermal, and mechanical techniques of ice removal are time-consuming and costly. The use of nanotextured coatings infused with perfluorinated oil has recently been proposed as a simple passive antifrosting and anti-icing method. However, we demonstrate that the process of freezing subcooled condensate and frost formation on such lubrican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
294
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(295 citation statements)
references
References 57 publications
1
294
0
Order By: Relevance
“…The observed switchable freezing temperature is in contradiction to the long standing point of view, that electric fields do not necessarily support the freezing process or will increase the freezing temperature. In contrast to the method presented here the water system in previously-described investigations [20] was cooled down to a supercooled state and an electric field was applied to this supercooled water system or alternatively water was cooled down in the presence of an external field [21]. In this work, however, the establishment of an electric field is part of the cooling process and takes place at the same time as the crystallization process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed switchable freezing temperature is in contradiction to the long standing point of view, that electric fields do not necessarily support the freezing process or will increase the freezing temperature. In contrast to the method presented here the water system in previously-described investigations [20] was cooled down to a supercooled state and an electric field was applied to this supercooled water system or alternatively water was cooled down in the presence of an external field [21]. In this work, however, the establishment of an electric field is part of the cooling process and takes place at the same time as the crystallization process.…”
Section: Discussionmentioning
confidence: 99%
“…Another appropriate approach represents switchable hydrophobic-hydrophilic and swellable surfaces working as a sponge-like liquid reservoir [17][18][19]. Combined inflexible and flexible layers based on oil trapped in silicon structures have at present a limited number of operational cycles due to oil depletion or water penetration into the substrate [20] and have limited application due to the risk of frost damage in a similar manner to the porous structures mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…under a very wide range of atmospheric conditions, may be very limited [1,2,13,16,22,33]. In a similar way, a recent study reported by Rykaczewski and coauthors [34] also raised doubts about the universal use of another class of rough anti-icing materials, i.e. so-called lubricant-impregnated surfaces (having rough surfaces infused with water-immiscible liquid).…”
mentioning
confidence: 84%
“…Lubricant-infused nano-/micro-structured surfaces have been recently introduced as an alternative approach to omniphobic materials [1][2][22][23][25][26][27][28][29][30]. The key feature of this design is the anchoring of a lubricating liquid into a chemically similar, texturized solid substrate, thus creating a stable, smooth, defect-free and liquid-repellent interface.…”
Section: Introductionmentioning
confidence: 99%